Community-Based Improvements to Increase Identification of Pregnant Women and Promote Linkages to Antenatal and HIV Care in Mozambique. (20th June 2019) - Stover, Kim Ethier; Shrestha, Ram; Tsambe, Isac; Mathe, Percina Paulo
A Community Health System Strengthening model, which mobilizes communities by applying quality improvement, was used in 39 communities around 3 health centers in Gaza Province, Mozambique, to increase identification of pregnant women and support them to attend antenatal care (ANC). This article describes the process and results. Community group representatives formed a community improvement team to spread messages about the importance of ANC, identify pregnant women, link them to the facility, and follow up. Between March 2014 and February 2015, teams identified 2020 pregnant women. Antenatal care attendance increased at all 3 centers. One health center did an additional chart review and found that postintervention, women were enrolling in care earlier in pregnancy. There were no changes in HIV testing or treatment initiation for HIV-positive women. Community-led improvement initiatives play an important role in connecting pregnant women with services to receive testing and treatment to promote optimal health and prevent HIV transmission.